2016
DOI: 10.1038/srep34253
|View full text |Cite
|
Sign up to set email alerts
|

Changes in disc status in the reducing and nonreducing anterior disc displacement of temporomandibular joint: a longitudinal retrospective study

Abstract: Treatment procedures for anterior disc displacement (ADD) of temporomandibular joint (TMJ) are far from reaching a consensus. The aim of the study was to evaluate disc status changes of anterior disc displacement with reduction (ADDWR) and without reduction (ADDWoR) comparatively, to get a better understanding of the disease progress without intervention. This longitudinal retrospective study included 217 joints in 165 patients, which were divided into ADDWR group and ADDWoR group based on magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 38 publications
1
28
0
1
Order By: Relevance
“…Another study with 92 TMJ from patients with DDWR (mean age 20.76 years) that underwent a follow-up of 9.38 months without treatment, showed that only 6 (6.5%) TMJ evolved into DDWoR. In the remainder, 86 (93.5%) DDWR temporomandibular joints, the disc length was evaluated, and the results showed a reduction of 0.66±0.97 mm after the follow-up (in the same study, 131 TMJ with DDWoR showed a decrease of 1.36±1.48 mm in disc length) 44 . A recent longitudinal study showed that of the 155 TMJ that had baseline diagnoses of normal/indeterminate or DDWR (and who received no treatment), 137 (88.4%) had no change in diagnosis 7.9 years later, on average; this result collaborates with previous studies that state that the classic model of DDWR progression to another internal derangement (such as DDWoR) is uncommon 45 …”
Section: Literature Reviewmentioning
confidence: 80%
“…Another study with 92 TMJ from patients with DDWR (mean age 20.76 years) that underwent a follow-up of 9.38 months without treatment, showed that only 6 (6.5%) TMJ evolved into DDWoR. In the remainder, 86 (93.5%) DDWR temporomandibular joints, the disc length was evaluated, and the results showed a reduction of 0.66±0.97 mm after the follow-up (in the same study, 131 TMJ with DDWoR showed a decrease of 1.36±1.48 mm in disc length) 44 . A recent longitudinal study showed that of the 155 TMJ that had baseline diagnoses of normal/indeterminate or DDWR (and who received no treatment), 137 (88.4%) had no change in diagnosis 7.9 years later, on average; this result collaborates with previous studies that state that the classic model of DDWR progression to another internal derangement (such as DDWoR) is uncommon 45 …”
Section: Literature Reviewmentioning
confidence: 80%
“…In our clinic, we also found that patients with ADD often had condylar resorption of the TMJ. Besides, the longer ADD history, the more severe condyle resorption and dentofacial deformities 32,33 . All of the above-mentioned results indicate that juvenile ADD is a major causative factor for condylar resorption resulting in mandibular asymmetry and retrognathia.…”
Section: Discussionmentioning
confidence: 99%
“…We think this is because the disease course is relevant to our stage. That means the longer disease course, the higher ADD stage 33 . However when ADD patients were processed by suitable treatments, their prognosis became reversed.…”
Section: Discussionmentioning
confidence: 99%
“…MRI images were taken perpendicular (sagittal images) and parallel (coronal images) to the horizontal long axis of the condyle. Detail parameters about the TMJ MRI scans were reported in our previous study 17 21 .…”
Section: Methodsmentioning
confidence: 99%